Thermal analysis of wood-steel hybrid construction - Fonseca, E.M.M. (2014)
The main objective of this work is to provide the thermal analysis in wood-steel hybrid elements for building constructions under fire conditions. A transient thermal analysis with nonlinear material behaviour will be solved with ANSYS program. The use of wood-steel hybrid models has major advantages as increased fire resistance, and improved high strength. Wood is a lightweight material, easy to assemble, great architectural features, thermal and acoustic characteristics. However, the high vulnerability of wooden elements under fire action, involves evaluating their behaviour accurately. Its physical behaviour is conditioned by the charring layer formation, which may allow the insulation into the structural section. The steel is a current use material allowing high structural strength. However, steel is a non-combustible material, and when compared with wood is a very good conductor of heat. Consequently, the unprotected sections of steel under fire quickly heats, and the fire resistance decreases considerably. The numerical modelling of the hybrid models considers the analysis at high temperatures and the nonlinear material properties. Using a computer model, it will become possible to calculate the fire resistance of these hybrid elements, an important parameter for safety and design rules.